National Communism in the Soviet Union, 1918-28 - Gurevitz, Baruch, 1945- (Pitt Russian East European Ser., 1980)
A unique perspective on the question of how Marxism and the early Soviet Union dealt with issues of nationalism, viewed through The Jewish Communist Workers' Party, the Poale Zion.